2006
DOI: 10.1080/09540120600568731
|View full text |Cite
|
Sign up to set email alerts
|

A community-based rapid assessment of HIV behavioural risk disparities within a large sample of gay men in southeastern USA: A comparison of African American, Latino and white men

Abstract: Because the southeastern USA is experiencing a disproportionate HIV infection rate compared to other regions of the country, we explored HIV behavioural risk disparities by race/ethnicity among self-identifying gay men. Conceived and implemented as a community-based participatory research (CBPR) study, this rapid assessment collected demographic and HIV risk-behaviour data from men in five gay bars in the northwestern part of the state of North Carolina, using an assessment available in English and Spanish. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 21 publications
1
45
1
Order By: Relevance
“…Unfortunately, we did not link reports of unprotected sex with partner type; therefore, we are unable to determine if unprotected sex was with their primary partner or a casual partner. Nonetheless, our findings could suggest that prevention messages are not effectively reaching African American youth and conveying the importance of protecting oneself, even within a long-term relationship (Rhodes et al 2006). The finding that having been kicked out of home because of sexual orientation was correlated with unprotected sex only among African Americans could be reflective of the importance of a sense of community and belonging within the African American community, especially with respect to family (Williams et al 2004;Jiminez 2003;Stokes and Peterson 1998;Whitehead 1997;Billingsley and Caldwell 1991).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Unfortunately, we did not link reports of unprotected sex with partner type; therefore, we are unable to determine if unprotected sex was with their primary partner or a casual partner. Nonetheless, our findings could suggest that prevention messages are not effectively reaching African American youth and conveying the importance of protecting oneself, even within a long-term relationship (Rhodes et al 2006). The finding that having been kicked out of home because of sexual orientation was correlated with unprotected sex only among African Americans could be reflective of the importance of a sense of community and belonging within the African American community, especially with respect to family (Williams et al 2004;Jiminez 2003;Stokes and Peterson 1998;Whitehead 1997;Billingsley and Caldwell 1991).…”
Section: Discussionmentioning
confidence: 73%
“…Cultural variations in attitudes towards and practices of condom use have been demonstrated among adult MSM (Harawa et al 2004;Rhodes et al 2006). A number of factors have been associated with inconsistent condom use among African American and Hispanic MSM; however, ethnic differences in the predictors of unprotected sex have been reported.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Fewer studies, however, have focused on Hispanic MSM. Rhodes, Yee, and Hergenrather (2006) conducted a study that surveyed African American, Caucasian, and Hispanic MSM. The researchers found that Hispanic MSM were more likely to report inconsistent condom usage during anal intercourse and were less likely than the other groups of MSM to be tested for HIV infection.…”
Section: Condom Usagementioning
confidence: 99%
“…Such community-based approaches may be successful in reaching Latinos who are otherwise unlikely to access conventional services. For example, one group has examined the feasibility of reaching Latino men at risk for HIV through Latino soccer leagues in North Carolina (Rhodes et al 2006). Overall, these inventive strategies and the use of culturally sensitive case management, community health workers, and patient navigators (Vargas and Cunningham 2006), hold promise to improve HIV-positive Latinos' access to care.…”
Section: Health Literacy Among Hiv-positive Latinosmentioning
confidence: 97%